Avoiding dental urgencies in cancer patients: a case report (Research, Society and Development, 2021)
The oral manifestations of cancer are significant, both resulting from the disease and from the antineoplastic treatments instituted, as they can compromise the function, aesthetics and quality of life of these patients, or even interrupt the treatments. The aim of this study was to report a clinical case of a patient diagnosed with cancer in the head and neck region submitted to bimodal chemotherapy and chemotherapy and describe what measures should be taken to avoid dental urgencies in these patients. A 53-year-old male patient, alcoholic and smoker, presents type II diabetes mellitus, diagnosed with moderately differentiated squamous cell carcinoma in the supraglottic region; referred to the dental service of the Oncology Center of the University Hospital Oswaldo Cruz of the University of Pernambuco prior to the start of cancer treatment. There was a need for oral adequacy and a standard operating protocol for oral care was established for individuals undergoing anticancer therapy. After a few weeks of treatment, the patient presented oral complications, with this, the protocol was adjusted, and the operational protocol for the treatment of bone necrosis was instituted. Thus, the oral mucosa was quickly recovered and the other areas of the mouth remained intact. This report corroborates the literature by showing that the dental follow-up of cancer patients is essential to minimize or even inhibit possible complications resulting from the treatments, being essential to avoid dental urgencies, promote comprehensive and humanized cancer care, as well as quality of life of the patient.